2017
DOI: 10.1016/j.chb.2017.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationships between self-presentation and self-esteem of mothers in social media in Russia

Abstract: Majority of parents use social media platforms, with young mothers being the most active users. Academic research has only recently started addressing the impact of social media on mothers, although they are one of the most engaged online audiences. Instagram and Facebook perceived as positive types of social media, where users post positive content to increase encouraging response from their subscribers and thus enhance their self-esteem. This also relates to mothers portraying positive self-presentation onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 37 publications
2
35
0
1
Order By: Relevance
“…Feelings of stigma may also be propagated through the presence of unrealistic notions of motherhood; something that was a common source of distress in this study. As with previous research [65,70], women in this study often reported feeling under an enormous amount of pressure to live up to the image of the 'perfect mum' so often portrayed by social (and mainstream) media, and expressed experiencing significant anxiety when they were unable to live up to these ideals. Therefore, future online support should seek to reconceptualise a new maternal identity for women with PNA.…”
Section: Addressing Stigma and Disclosuresupporting
confidence: 69%
“…Feelings of stigma may also be propagated through the presence of unrealistic notions of motherhood; something that was a common source of distress in this study. As with previous research [65,70], women in this study often reported feeling under an enormous amount of pressure to live up to the image of the 'perfect mum' so often portrayed by social (and mainstream) media, and expressed experiencing significant anxiety when they were unable to live up to these ideals. Therefore, future online support should seek to reconceptualise a new maternal identity for women with PNA.…”
Section: Addressing Stigma and Disclosuresupporting
confidence: 69%
“…Feelings of stigma may also be propagated through the presence of unrealistic notions of motherhood; something that was a common source of distress in this study. As with previous research (66,72), women in this study often reported feeling under an enormous amount of pressure to live up to the image of the 'perfect mum' so often portrayed by social (and mainstream) media, and expressed experiencing significant anxiety when they were unable to live up to these ideals.…”
Section: Addressing Stigma and Disclosuresupporting
confidence: 69%
“…This may explain why the impact of friendship-contingent selfesteem is not as strong as self-esteem in general, even though general self-esteem relies on specific forms of it, like friendship-contingent self-esteem. Self-esteem in general has a strong influence on the online selfpresentation of individuals (Djafarova & Trofimenko, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Facebook and Instagram are the most frequently used social media applications to present oneself online in various forms (Djafarova & Trofimenko, 2017). This research focuses only on Instagram users, because Instagram is such a popular platform used by teenagers and adults, who are the researcher's targets.…”
Section: Introductionmentioning
confidence: 99%